An Introduction to Power BI - Mohammed Al-Saadi (9744608) (2025)
This Presentation was given by Mohamed Al-Saadi IFLA Center for Arab Libraries/ Transformation Pioneers, Business Consulting and Services, Oman (IFLA MENA 2025) This presentation introduces the fundamentals of Power BI and highlights its value as a data visualization and business intelligence tool in the field of library and information science. It explores key applications of Power BI in libraries, emphasizing its role in supporting data-driven decision-making, improving reporting processes, and streamlining daily operations. Through practical examples, the presentation will demonstrate how librarians can effectively use Power BI to enhance services and drive innovation. Other Information License: http://creativecommons.org/licenses/by/4.0/